Analysis of Operational Performance of Transjakarta Public Transportation Corridor 13 Route Puri Beta 2 - Latuharhari (L13e) - Rizki Adam Dawi; Nunung Widyaningsih (International Journal Labs, 2024)
Transportation is one of the state's tools to drive the economy, the Jabodetabek community already has a fairly good means of transportation, one of which is the Transjakarta Bus. Transjakarta buses have also developed their routes and one of the routes that is quite busy is Puri Beta 2 - Latuharhari corridor L13E. Although Transjakarta Route L13E is operated by Express, there are still problems with the frequency of bus arrivals. This is because the L13E route does not fully have a dedicated path. There are still some segments mixed with other traffic. The purpose of this study is to determine and analyze the Transjakarta Bus Performance of Puri Beta 2 – Latuharhari L13E Route. The method used for this research is a survey method to the field to obtain research data. After the data is obtained, then an operational performance analysis will be carried out on performance indicators based on the standards of the Decree of the Director General of Land Transportation No.SK.687 / AJ.206 / DRJD / 2002. From the results of the study of seven operational performance indicators referring to the Decree of the Directorate General of Land Transportation No.687 / AJ.206 / DRJD / 2002 obtained five indicators with category A (Good), namely: 1) Headway (time between), 2) Load Factor (Load Factor), 3) Travel speed, 4) Service Time, 5) Waiting time. While there are 2 indicators with category B (Medium), namely: 1) Frequency, 2) Travel Time. Based on the overall assessment of the Operational Performance of the Directorate General of Land Transportation Decree No.687/AJ.206/DRJD/2002, Transjakarta Bus L13E obtained an A or Good grade. Based on the calculation of the maximum load factor, it is found that the bus stop that has the highest number of passengers or maximum load factor on weekday morning direction 1 towards Latuharhari is Adam Malik stop to Velbak stop, this also happens on weekend morning direction 1 towards Latuharhari, this is because Adam Malik bus stop is a bus stop that is quite busy with universities and densely populated areas and is also one of the stops of choice for the surrounding community to travel to the center city. In this study, it was also found that the maximum load factor on Weekday afternoon direction 2 towards Puri Beta 2 occurred at the Patra Kuningan stop to the Velbak stop, this is because the Patra Kuningan stop is an office area and also the Velbak stop is one of the choices for service users to be able to move to other modes of transportation.